Municipal websites and information about the local implementation of a public reform - Olsen, Trude Høgvold; Solstad, Elsa (Scandinavian Journal of Public Administration, 2012)
In this article we focus on how Norwegian municipalities present information about the results of their work of implementing The Coordination Reform to the inhabitants through their websites. The point of departure is that political reforms may lead to uncertainty for the inhabitants. This uncertainty can partly be handled by giving specific information about how the reform will affect the inhabitants. We contribute to the debate about the municipality as an information agent by following how the 25 municipalities in Troms County cover their work on The Coordination Reform on their websites over a period of one year. We focus on external communication to a heterogeneous target group (the inhabitants) in a reform context. The main finding is that the municipalities disseminate relatively little information about their work with the reform and about specific results. But there are variations between the municipalities. It may seem that they wish to show that they focus on the reform in different ways and part of the information on the websites are therefore of symbolic character.